Eksplorasi Kecerdasan Kinestetik Anak Sekolah Dasar Lewat Video Tari Tradisional Cempe - Grudhowaringin, Dhirgan (Impressive: Journal of Education, 2025)
This study aims to describe dance learning in elementary schools using the Cempe dance video as a learning medium and to determine the stimulation of students' kinesthetic intelligence after using the media. The research employed a mixed-method approach: qualitative methods were used to describe the learning process, and quantitative methods with a one-group pretest-posttest design were applied to measure changes in students’ kinesthetic intelligence. The research subjects were first and second-grade students from two elementary schools in Malang and Blitar, totaling 30 students. Data were collected through observation and interviews using validated instruments, which showed a "very valid" result (94.4%). Pretest results indicated that students had difficulty imitating movement. After treatment—watching the Cempe dance video supported by teacher demonstrations and the mirror method—posttest scores showed significant improvement. The t-test results showed that the t-value (32.56) was greater than the t-table (2.04), indicating a significant effect of using the Cempe dance video on enhancing students' kinesthetic intelligence. Learning designed to be enjoyable, interactive, and visually engaging was proven to boost students' motivation and active participation. This study highlights the importance of audio-visual media in elementary dance education to support the development of students’ motor skills and expressive abilities